Being a judge in the modern world - Cooper, Jeremy, 1950- (Oxford University Press, 2017)
The role of the judiciary is constantly evolving and is in many ways more important than ever. Indeed, many argue that the sovereignty of parliament is eroding and being replaced by the respective power of judges. The Jackson Reforms of 2010, for example, saw judges bestowed with more power over case and budget management than ever before. Equally, courtrooms are transforming under the weight of technological innovation and the increasing presence of litigants in person. Stemming from a series of lectures arranged by the Judicial College on the theme of 'Being a Judge in the Modern World', this book provides a survey of many significant aspects of the modern judicial role. With contributions from some of the most senior judges in the UK and beyond, this collection provides a unique and firsthand insight into the development of the legal system and the challenges faced by today's judiciary. Additional contributions from the realms of journalism and civil liberties offer an external perspective and provide a wider context to the judicial voices. --